PENGARUH PEMBERIAN KOMPOS KULIT KOPI DAN PUPUK NPK MUTIARA TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS ( ZEA MAYS SACCHARATA L.) DI SIMALUNGUN - IRAWATY ROSALYNE (LP2MTBM MAKARIOZ, 2022)
The study used a randomized design of the group (RAK) factorial with two factors, the first factor is the composting of coffeeskin, namely: K0: Control (without the provision of coffee skin compost), K1: 2 kg / plot, (6.3 tons / ha) coffee skin compost,K2: 4kg / plot, (12.6 tons / ha) coffee skin compost, K3: 6kg / plot, (18.9 tons / ha) coffee skin compost and the second factoris the provision of NPK fertilizer consisting of N1: 0.10 kg/NPK fertilizer plot,N2: 0.20 kg/NPK fertilizer plot,N3: 0.30 kg/NPKfertilizer plot. Parameters observed in this study include: plant height (cm), stem diameter, sample soil cob weight and cobweight per plot. The composting of coffee skin has a real effect on all observation parameters, treatment interactions, as wellas the provision of NPK fertilizer except the diameter of the stem. The K3N3 treatment showed the highest plant height ofobservation ages of 3.6, and 9 MST, respectively (77.74cm), (198 cm), and (248.57cm). corn cob weight per sample (361.47g or 20.65 tons/ha), and fruit cob weight per plot (6.50 kg, or 20.63 tons/ha). In the treatment K2N3 shows the diameter ofthe highest rod (2.49 cm).